Commentary on the papers. (2nd January 2017) - Howe, Christine; Mercer, Neil
ABSTRACT: This commentary discusses the four papers that comprise the special issue on dialogic teaching and learning, while making general observations that apply across the field as a whole. Similarities and differences are identified over the concepts of 'dialogue' and 'dialogic pedagogy'. The possibility is raised that some aspects of dialogic pedagogy are more tractable than others, perhaps because they are more readily mapped onto traditional practices. The implications of this for analysing the dialogue-learning relation are considered. Attention is paid to the relevance for classroom dialogue of topic, epistemology, multilingualism, and the wider socio-political context. Finally, the challenge of scalability is addressed, in particular the need for cost-effective methods of teacher professional development if dialogic pedagogy is ever to become widely embedded in classrooms.